The banana Xanthomonas wilt epidemic in east and central Africa: current research and development efforts - Tinzaara, William; Karamura, E.B.; Kubiriba, Jerome; Ochola, D.; Ocimati, W.; Blomme, Guy; Ssekiwoko, F. (International Society for Horticultural Science, 2016)
Xanthomonas wilt is currently the major biotic threat to banana production in East and Central Africa (ECA). The recommended management options for the disease include destruction of infected plants, disinfecting tools used in the plantation, using clean planting materials, early removal of male buds and quarantine measures. These efforts to control the disease have produced partial success and the disease has continued to encroach into previously disease-free areas and to resurge in areas where it had been controlled. One of the major challenges to sustainable management of the disease has been poor understanding by stakeholders of the factors influencing disease spread. Current research efforts aim to provide additional information on disease epidemiology, fine tune existing cultural control practices, identify resistant and wilt escaping genotypes and develop a field detection tool. Development activities that aim at effective mobilization of stakeholders along the value chain for sustainable management of the disease (including use of farmer field schools (FFS) and learning and experimenting approaches for farmers (LEAFF)) have been evaluated and or implemented in ECA. In this paper, we discuss the different regional research and development efforts for the management of BXW. New research directions for sustainable management of BXW in ECA are suggested, including development of resistant banana cultivars through genetic engineering; exploring the potential use of endophytes as biological control agents; and studying modelling factors influencing BXW dynamics. Persistent challenges to managing BXW include: insufficient knowledge of the disease epidemiology critical for developing management strategies, inadequate mobilization and sensitization of the key stakeholder platforms along the production-consumption chain, ineffective surveillance methods leading to untimely actions, and lack of healthy BXW resistant seed. There is therefore need for continued research efforts and innovative approaches to effectively mobilize all stakeholders along the banana value chain.